Delusional infestation in healthcare professionals: Outcomes from a multi‐centre case series. Issue 4 (28th November 2022) - Frewen, John; Lepping, Peter; Goulding, Jonathan M. R.; Walker, Stephen; Bewley, Anthony
Abstract: Delusional infestation (DI) describes an unwavering fixed belief of infestation with pathogens, despite a lack of medical evidence supporting this. Effective management of DI with antipsychotics is made challenging by the fixed belief that the condition is an infestation or infection rather than a mental illness. A case series of individuals diagnosed with DI included 11% who were healthcare professionals (HCPs). We sought to characterise a cohort of HCPs who presented with DI in the UK. The case notes of HCPs diagnosed with DI at specialist clinics between 2015 and 2019 were reviewed. Demographic and clinical data were obtained. Twelve HCPs were identified out of a total of 381 individuals diagnosed with DI. Median age was 52.5 (IQR = 14.5) years. 75% ( n  = 9) were women. Ten individuals had primary DI, whilst two had secondary DI (one to recreational drug use, one to depression). Four individuals (33%) engaged with antipsychotic treatment. Two responded well, both had secondary DI. Of the two individuals with primary DI who engaged, one did not respond to antipsychotic medication and the other was unable to tolerate two antipsychotic drugs. In Primary DI ( n  = 10), the rate of adherence was lower at 20% ( n  = 2). In DI, high engagement and adherence rates to treatment have been reported in specialist centres. Improvement has been reported as high as 70%–75%. This indicates that a large proportion of individuals who adhere to treatment appear to derive benefit. In this series, engagement with treatment by HCPs with primary DI was low at 20%, and improvement was only achieved in individuals with secondary DI. Mental illness‐related stigma, feelings of distress and difficulty forming therapeutic relationships with a professional peer are significant challenges. Developing rapport is key to treatment success in DI. In HCPs this may be suboptimal due to these negative feelings, resulting in lower engagement. A diagnosis of DI in a HCP may raise concerns regarding fitness to practise. An assessment of the impact of DI and the potential to interfere with professional duties warrants consideration. We highlight the occurrence of DI in HCPs, and the apparent lower engagement with treatment in this cohort.